Representing dynamic dimensions in OLAP cubes - Panchenko, T.V. (Інститут програмних систем НАН України, 2015)
Two well-known approaches to modelling the dynamic dimensions are considered: a model with many-to-many relationship between the dimension hierarchy elements as well as Slowly Changing Dimensions. A method of independent dimensions creating for the dynamic dimensions modelling in the OLAP-cubes is proposed. It is proved that the method has a lower model development complexity because of idea clearance. The comparative analysis of three methods is given here.